A designer support framework for specification comprehensibility in automata-based discrete-event control design - Amrith Dhananjayan (2013)
This thesis addresses the longstanding problem of comprehensibility in formal language specification for supervisory control of logical and real-time discrete-event systems (DES’s). The problem stems from control designers who often face the dilemma of not knowing if a manually prescribed specification in finite automata is the intended control requirement. The need to validate such a specification by checking whether or not it is as intended requires formal theoretical support. With the availability of increasingly efficient algorithms and tools that are predominantly based on finite automata for specification and control synthesis, the challenges posed by human designer comprehensibility have been identified as one of the major reasons limiting the adoption of supervisory control theory for solving complex industrial problems. To mitigate this problem, this thesis proposes a new specification comprehensibility framework that provides designer support for writing and validating both logical and real-time specifications from the following two perspectives: